1994
DOI: 10.1111/j.1476-5381.1994.tb14840.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of PGE2 by bovine cultured airway smooth muscle cells and its inhibition by cyclo‐oxygenase inhibitors

Abstract: 1 Prostaglandin E2 (PGE2) is thought to be an important inhibitory modulator of inflammatory processes in the airway. It inhibits inflammatory cell function and cholinergic neurotransmission in vitro and roles have been postulated in vivo in refractoriness and in the mechanism of action of the diuretic agent, frusemide. 2 The production of PGE2 by bovine cultured airway smooth muscle cells has been studied under a range of conditions. The effects of cyclo-oxygenase inhibitors (flurbiprofen, indomethacin, acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 25 publications
2
42
1
Order By: Relevance
“…Prostaglandin E 2 assay PGE 2 concentration was determined by radioimmunoassay as previously described [31]. The authors have previously validated this assay [22,23,31] and have shown it to have a low cross-reactivity with other metabolites of AA [22,23].…”
Section: Cyclo-oxygenase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin E 2 assay PGE 2 concentration was determined by radioimmunoassay as previously described [31]. The authors have previously validated this assay [22,23,31] and have shown it to have a low cross-reactivity with other metabolites of AA [22,23].…”
Section: Cyclo-oxygenase Activitymentioning
confidence: 99%
“…The authors have previously validated this assay [22,23,31] and have shown it to have a low cross-reactivity with other metabolites of AA [22,23]. Each sample analysed for PGE 2 was assayed in duplicate.…”
Section: Cyclo-oxygenase Activitymentioning
confidence: 99%
“…However, blockade of PGE 2 production leads to partial reversal of β 2 AR desensitization in the context of inflammation (3), and thus PGE 2 may promote bronchoconstriction via desensitization of β 2 AR function or by activation of the G q -coupled EP 1 receptor. PGE 2 is produced by ASM, airway epithelial cells, and inflammatory cells and is the most abundant prostanoid in epithelial lining fluid (4)(5)(6). However, EP 1 -mediated signal transduction and its effect on airway responsiveness remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Bradykinin (BK) stimulates PGE # synthesis and release in cultured bovine ASM cells [7]. In this regard, PGE # might…”
Section: Introductionmentioning
confidence: 99%